Andean customary law in the Peruvian legal system. An approach from a university education perspective - Puma Llanqui, Javier Santos (2022)
The legal system of the states is built on the basis of the uses and customs of the population; however, in the Peruvian legal system, the Greco-Roman tradition is imposed, leading to the clandestinity of customary law. The objective of this research is to demonstrate the academic formation of law in public and private universities in Peru through the analysis of the curricula. The method used was the documentary review available on the website of the National Superintendence of University Higher Education - SUNEDU. According to the results, in Peru, 29.8% of the faculties that train law professionals correspond to public universities and 70.2% to private universities. Of these, 70.24% state that Roman law and common law are mandatory subjects, while 71.4% do not consider courses on legal pluralism or common law. Therefore, the professional training in law and therefore, the administration of justice is not in accordance with the context, due to the fact that in recent years serious crises and social conflicts have been unleashed with backgrounds of cultural inequalities. Therefore, Andean customary law should be considered as a relevant subject in the Peruvian university education of future lawyers, who will impart justice in a population that self-identifies as indigenous.